Pelatihan Identifikasi Anak Berkebutuhan Khusus di Sekolah Inklusi: Upaya Mendukung Kebijakan Education For All - Muya Barida; Dian Ari Widyastuti (Bagimu Negeri, 2019)
The development of the inclusive education system in schools programmed by the Government demands changes in teacher competencies in identifying students including special need children (SNC). In fact, the teacher's ability to identify SNC is still minimal. Therefore, planned training was carried out regarding the identification of SNC. The implementation of this training can improve the ability of teachers to identify special need children. This can be known based on the values of the pretest and posttest. At the pretest the average value was 62, while at the posttest the average score was 79, it can be concluded that the training for identifying children with special needs is still very necessary for all teachers in Indonesia.